2009
DOI: 10.1007/s00213-009-1710-5
|View full text |Cite
|
Sign up to set email alerts
|

Histamine and H3 receptor-dependent mechanisms regulate ethanol stimulation and conditioned place preference in mice

Abstract: Histaminergic neurotransmission seems to be necessary for the stimulatory effect of ethanol to occur, whereas lack of histamine leads to changes that enhance the conditioned reward by ethanol. Our findings also suggest a role for histamine H3 receptor in modulation of the ethanol stimulation and reward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 62 publications
7
40
2
Order By: Relevance
“…However, changes in the DA neuron activity do not necessarily produce a response in DA release, and it is also possible that different mesolimbic VTA DA neuron populations separately mediate rewarding and aversive behaviors (Lammel et al, 2011). Indeed, repeated GAN administrations in an unbiased place-conditioning paradigm resulted in aversion rather than preference for conditioned floors in C57BL/6J mice, with which we have previously seen significant morphine-and ethanol-induced conditioned preference Nuutinen et al, 2010). Further, we have found that THIP induces prolonged conditioned aversion in mice and that it fails to sustain reinforcement behavior in baboons, in contrast to benzodiazepines (Vashchinkina et al, 2012).…”
Section: Failure To Induce a Cppmentioning
confidence: 94%
“…However, changes in the DA neuron activity do not necessarily produce a response in DA release, and it is also possible that different mesolimbic VTA DA neuron populations separately mediate rewarding and aversive behaviors (Lammel et al, 2011). Indeed, repeated GAN administrations in an unbiased place-conditioning paradigm resulted in aversion rather than preference for conditioned floors in C57BL/6J mice, with which we have previously seen significant morphine-and ethanol-induced conditioned preference Nuutinen et al, 2010). Further, we have found that THIP induces prolonged conditioned aversion in mice and that it fails to sustain reinforcement behavior in baboons, in contrast to benzodiazepines (Vashchinkina et al, 2012).…”
Section: Failure To Induce a Cppmentioning
confidence: 94%
“…CPP paradigm was used as described in (Nuutinen et al, 2010a) and it followed the principles of an unbiased, fully counterbalanced conditioning described by (Cunningham et al, 2006). Conditioning cages were individual transparent plastic cages (42 Â 26 Â 20 cm) covered with clear plastic lids with ventilation holes.…”
Section: Alcohol-induced Cppmentioning
confidence: 99%
“…Treatment with H3R antagonists suppresses alcohol drinking in alcohol-preferring rats (Lintunen et al, 2001;Galici et al, 2010) and inhibits alcohol reward in a conditioned place preference (CPP) paradigm in mice (Nuutinen et al, 2010a). The H3R antagonists themselves are not rewarding or aversive (Nuutinen et al, 2010a;Munzar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations